2021
DOI: 10.1177/0972150921993674
|View full text |Cite
|
Sign up to set email alerts
|

Peer Effects on Investment Decisions: Do Industry Leaders and Young Firms Behave Differently?

Abstract: This study examines the influence of peer firms on a firm’s investment policy in Pakistan during the period 2001–2017. It also investigates the heterogeneity in peer effects by taking into account a firm’s age and its leadership role in the industry. The system-GMM estimation results suggest that peer firms significantly influence a firm’s investments on both tangible and intangible assets. Yet, peer effects are more pronounced for tangible investment. We also observe that young firms are more prone to imitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…The finance literature has found a significant and positive influence of firm size on dividend payouts (Gul et al, 2020) and suggests that larger companies are more likely to pay dividend payouts (Franc-Dabrowska and Madra, 2020). However, the literature has found that new companies are more likely to mimic their industry peers' decisions (Rashid and Said, 2021). Consistent with Lieberman and Asaba (2006), this study examines which of these theories is supported by the Pakistan Stock Exchange (PSX) firms.…”
Section: Influence Of Peer Firms' Payouts On Firm Payout: Role Of Fir...mentioning
confidence: 78%
See 1 more Smart Citation
“…The finance literature has found a significant and positive influence of firm size on dividend payouts (Gul et al, 2020) and suggests that larger companies are more likely to pay dividend payouts (Franc-Dabrowska and Madra, 2020). However, the literature has found that new companies are more likely to mimic their industry peers' decisions (Rashid and Said, 2021). Consistent with Lieberman and Asaba (2006), this study examines which of these theories is supported by the Pakistan Stock Exchange (PSX) firms.…”
Section: Influence Of Peer Firms' Payouts On Firm Payout: Role Of Fir...mentioning
confidence: 78%
“…The estimated coefficient of the peer dividend payout ratio is significantly positive in both big (β=0.0098, P>1%) and small (0.1723, P>5%) firms but the magnitude of this impact appears to be greater among small companies. The results indicate that the effect of peers on firm payouts is greater among smaller firms, implying that mimicking the dividend payout decision was significant primarily for younger and smaller firms (Rashid and Said, 2021). However it is not surprising that most dividend payers are big firms because the big firms appear to be more pressured to mimic major positive adjustments in dividends (Adhikari, 2013).…”
Section: Peer Influence On Firm Payouts: Role Of Firm Sizementioning
confidence: 91%
“…Strong group effects will lead to excessive debt and overinvestment by companies, thereby weakening their debt repayment, profitability, and other issues. Starting from the causes of group effects, the authors analyze the issue of excessive corporate debt and provide strategies and recommendations [21]. Scholars have extended the study of group effects to government policy formulation, which goes beyond the corporate level.…”
Section: Mechanisms Of Homophily In Information Disclosure Behaviormentioning
confidence: 99%